Static Leukoencephalopathy Associated with 17p13.3 Microdeletion Syndrome: A Case Report - Hirasawa-Inoue, Ayaka; Takeshita, Eri; Shimizu-Motohashi, Yuko; Ishiyama, Akihiko; Saito, Takashi; Komaki, Hirofumi; Nakagawa, Eiji; Sugai, Kenji; Inoue, Ken; Goto, Yu-ichi; Sasaki, Masayuki (Neuropediatrics, 2019)
Background Leukoencephalopathy associated with dysmorphic features may be attributed to chromosomal abnormalities such as 17p13.3 microdeletion syndrome.Case A 19-year-old female patient was referred to our hospital for diagnostic evaluation of her leukoencephalopathy. She demonstrated moderate intellectual disability, minor dysmorphic features, and short stature. Serial brain magnetic resonance images obtained within a 16-year interval revealed prolonged T2 signals in the deep cerebral white matter with enlarged Virchow–Robin spaces. A nonsymptomatic atlas anomaly was also noted. Using microarray-based comparative genomic hybridization, we identified a 2.2-Mb terminal deletion at 17p13.3, encompassing YWHAE, CRK, and RTN4RL1 but not PAFAH1B1.Conclusion Except for atlas anomaly, the patient's clinical and imaging findings were compatible with the diagnosis of 17p13.3 microdeletion syndrome. The white matter abnormality was static and nonprogressive. The association between the atlas abnormality and this deletion remains elusive. We note the importance of exploring submicroscopic chromosomal imbalance when patients show prominent but static white matter abnormalities with discrepantly mild and stable neurological signs.
Keywords: 17p13.3 microdeletion; YWHAE; PAFAH1B1; leukoencephalopathy; Virchow–Robin space